Política industrial e empresas estatais no Brasil: BNDES e Petrobras - Mansueto Almeida; Renato Lima-de-Oliveira; Ben Ross Schneider (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The return of the developmental State in Brazil raises revealing historical and comparative contrasts. The main contemporary difference is that developmentalism and industrial policy are being defined and pursued in far more open and participatory political contexts than was previously the case in either Brazil or East Asian cases and more open borders in terms of economic flows of trade, finance, and direct investment. In the 20th century, governments could more easily focus on designing and implementing industrial policy. Democratic governments in the 21st century, in contrast, manage a host of other, especially social, policies. These policies of course compete with industrial policy for both resources and top level political support. This paper investigates how industrial policies are designed, implemented and evaluated today in Brazil, focusing on two Brazilian State companies, BNDES and Petrobras, the two largest and most active agents of industrial policy in Brazil.
Keywords: H25; L52; L53; 330; industrial policy; state companies; developmental State; BNDES; Petrobras